Sustentabilidade energética do etanol de primeira geração no Brasil : uma releitura crítica de referenciais metodológicos - Lee, Lisiong Shu (2017)
In the long run, all fossil energy, such as oil, natural gas, coal, and radioactive material, will run out. Within a horizon of one or two centuries, all energy must come from renewable sources. The concept of sustainable energy, without fossil energy, relies on the tripod speed of energy formation, environmental impacts corrected in the production period, and maintenance of physical and social well-being for millennia. The only renewable energy source that meets all requirements is the energy from the sun. Even the hydraulic energy, used since the time of the ancient Greeks, is an indirect solar energy, and is a mature technology. Nascent technologies allow capture solar energy in the following ways: as biomass, as electricity using photovoltaic and wind technologies, and as heat by concentrating solar energy. The four alternatives provide convenient secondary energy: liquid fuels and electricity. In Brazil, sugarcane, a C4 photosynthesis plant, presents high productivity in terms of tons per hectare per year, and high sugar content per ton of sugarcane. In the ethanol production process, bagasse generated as a by-product is used to obtain energy (thermal and electric) for self consumption. Ethanol is produced by the fermentation of the sugarcane juice, which contains mainly sucrose. To what extent is ethanol sustainable according to the tripod mentioned above? There are many studies on the sustainability of sugarcane ethanol, with indicators such as the relation between fossil energy used and useful energy, CO2eq emissions, and environmental impacts of residues such as vinasse and filter cake. These studies implicitly assume that there is abundant fossil energy. They report an EROI (Energy Return Over Invested) between 8 and 11. Few authors report an EROI in the range of 3 to 5. This dissertation includes co-product credits as surplus electricity, and assumes the use of the best industrial technology. Special care was devoted to verifying values and consistency of the primary data, with record of maximum value, minimum value, and value adopted with justification. Each secondary value has been documented with calculation methodology, allowing reproducibility of the results by any researcher. The result was an EROI of 1.67. It is also noted that Brazil would not have enough land or agricultural inputs to produce all the energy consumed during year 2015. Ethanol production, while contributing significantly to the absorption of carbon dioxide from the atmosphere, will need to be complemented by other sustainable energy production technologies that use less physical resources.